2021
DOI: 10.3390/diagnostics11071159
|View full text |Cite
|
Sign up to set email alerts
|

Does Anatomical Contextual Information Improve 3D U-Net-Based Brain Tumor Segmentation?

Abstract: Effective, robust, and automatic tools for brain tumor segmentation are needed for the extraction of information useful in treatment planning. Recently, convolutional neural networks have shown remarkable performance in the identification of tumor regions in magnetic resonance (MR) images. Context-aware artificial intelligence is an emerging concept for the development of deep learning applications for computer-aided medical image analysis. A large portion of the current research is devoted to the development … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…ASPP has been employed in various studies within brain segmentation. However, as per Tampu et al ( 28 ), boosting context alone does not increase the performance of the model.…”
Section: Methodsmentioning
confidence: 74%
“…ASPP has been employed in various studies within brain segmentation. However, as per Tampu et al ( 28 ), boosting context alone does not increase the performance of the model.…”
Section: Methodsmentioning
confidence: 74%
“…These findings are in line with a recent study from Ladefoged et al (25) in which an artificial neural network was developed and trained on 18 F-FET PET and MRI scans from 233 adult brain tumor patients and applied to a dataset of 66 pediatric brain tumor patients for automated tumor segmentation. The authors also found the largest relative errors for tumor segmentations for small tumors with a volume of less than 10 cm 3 . Although the network demonstrated excellent performance in pediatric tumor patients, a few cases were reported in which the network erroneously delineated anatomic regions showing a high physiologic uptake.…”
Section: Discussionmentioning
confidence: 90%
“…However, due to their smaller sizes, irregular shapes, and similar textures to the surrounding tissues, enhanced and core tumors remain complex challenges in terms of reliable segmentation [ 2 ]. To date, none of the currently available methods, including [ 2 , 13 , 15 , 16 , 17 , 18 ], have achieved the same level of performance for ET and TC region segmentation (regarding the whole tumor region).…”
Section: Introductionmentioning
confidence: 99%